Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{24}{x}\div\frac{8}{3}=\frac{3}{5}\)
\(\frac{24}{x}\cdot\frac{3}{8}=\frac{3}{5}\)
\(\frac{24}{x}=\frac{3}{5}\div\frac{3}{8}\)
\(\frac{24}{x}=\frac{24}{15}\)
Vậy x = 15
b) Tương tự
a.\(\frac{11}{14}-\frac{3}{x-1}=\frac{5}{14}\)
\(\frac{3}{x-1}=\frac{11}{14}-\frac{5}{14}\)
\(\frac{3}{x-1}=\frac{3}{7}\)
\(\Rightarrow x-1=7\)
\(x=7+1\)
Vậy \(x=8\)
b.\(\frac{42}{25}:\frac{2x+1}{5}=\frac{6}{5}\)
\(\frac{2x+1}{5}=\frac{42}{25}:\frac{6}{5}\)
\(\frac{2x+1}{5}=\frac{7}{5}\)
\(\Rightarrow2x+1=7\)
\(2x=7-1\)
\(2x=6\)
\(x=6:2\)
\(x=3\)
a.\(\frac{11}{14}-\frac{3}{x-1}=\frac{5}{14}\)
\(\frac{3}{x-1}=\frac{11}{14}-\frac{5}{14}=\frac{3}{7}\)
\(\Rightarrow x-1=7\)
\(x=7+1=8\)
VẬY, \(x=8\)
b. \(\frac{42}{25}:\frac{2x+1}{5}=\frac{6}{5}\)
\(\frac{2x+1}{5}=\frac{42}{25}:\frac{6}{5}=\frac{7}{5}\)
\(\Rightarrow2x+1=7\)
\(2x=7-1=6\)
\(x=6:2=3\)
VẬY, \(x=3\)
Erza
a) \(\frac{3}{5}-\frac{1}{3}-\frac{1}{6}=\frac{18}{30}-\frac{10}{30}-\frac{5}{30}=\frac{18-10-5}{30}=\frac{1}{10}\)
b) \(\frac{4}{7}\times\frac{5}{8}\times\frac{7}{12}=\frac{4\times5\times7}{7\times8\times12}=\frac{140}{672}=\frac{5}{24}\)
c) \(\frac{25}{28}\div\frac{15}{14}\times\frac{6}{7}=\frac{25}{28}\times\frac{14}{15}\times\frac{6}{7}=\frac{25\times14\times6}{28\times15\times7}=\frac{2100}{2940}=\frac{5}{7}\)
Thấy đúg thì tk nha các bn !!
a,3/5 - 1/3 - 1/6
= 4/9 - 1/6
= 5/9
b,4/7x5/8x7/12
= 5/14 x 7/12
= 5/24
c,25/18 :15/14 x 6/7
= 25/28 x 14/15 x 6/7
= 5/6 x 6/7
= 5/7
(x-1/2)*5/3=7/4-1/2
(x-1/2)*5/3=5/4
x-1/2=3/4
x = 5/4
(x+4/3)*7/4=5-7/6
(x+4/3)*7/4=23/6
x+4/3 = 46/21
x = 6/7
6/8=15/x
6*x=15*8
6*x=120
x = 20
\(\frac{6}{8}=\frac{15}{x}\)
\(\Rightarrow x=\left(15\cdot8\right):6\)
\(\Rightarrow x=20\)
a,
x.2/7.3/4=5/21
x.3/14=5/21
x=5/21:3/14
x=10/9
b,
x.1/2=1/3
x=1/3:1/2
x=2/3
c,
x:4/5=25/8:5/4
x:4/5=5/2
x=5/2.4/5=2
A, x= 5/25 : 3/4 : 2/7 = 14/15
B, x=1/3 : 1/2 = 2/3
C, x=(25/8 : 5/4)x4/5 = 5/2 x 4/5 = 2
\(\frac{x}{7}\)= \(\frac{42}{45}\): \(\frac{6}{5}\)= \(\frac{7}{9}\)
x = 7 x \(\frac{7}{9}\)
x = \(\frac{49}{9}\)
Ta có: \(\frac{42}{45}:\frac{x}{7}=\frac{6}{5}\)
\(\Rightarrow\frac{x}{7}=\frac{42}{45}:\frac{6}{5}=\frac{7}{9}\)
=> x = 7 x 7 : 9
=> x = \(\frac{49}{9}\)
Vậy x = \(\frac{49}{9}\)
Xx11/5-Xx4/7=5/77
Xx(11/5-4/7)=5/77
Xx57/35=5/77
x=5/77:57/35=25/627